Narracyjny portret Marie Grubbe w powieści Lone Hørslev "Dyrets år" (Rok bestii) - Cymbrykiewicz, Joanna (Folia Scandinavica Posnaniensia, 2016)
The article A narrative portrait of Marie Grubbe in Lone Hørslev’s novel Dyrets år (The Year of the Beast) discusses the latest biographical novel on the controversial Danish aristocrat from the 17th century. In order to address the issue in closer detail, a brief biography of Marie Grubbe is given in the article’s introduction which is followed by a presentation of all the Danish works of fiction on the person that have been published so far. The analysis shows that the authors’ approach to their protagonist varies from disgust to fascination, depending on the period that the work originates from. Lone Hørslev’s Dyrets år may not be a genuine masterpiece, but it definitely adds new, contemporary aspects to the overall understanding of Marie Grubbe’s conduct and enriches her portrait with some traits which have not yet been discussed.